The Effectiveness of Learning Videos to Improve Elementary School Teachers' Understanding of the Learning Characteristics of Students with Special Needs - Kartini, Ade; Aprilia, Imas Diana; Rochyadi, Endang (Department of Special Education, 2024)
The lack of understanding of elementary school teachers about the learning characteristics of students with special needs and the lack of adaptive learning media is allegedly factors that do not optimize learning. This study aims to measure the effectiveness of learning videos in improving elementary school teachers' understanding of the learning characteristics of students with special needs. The research method used is descriptive quantitative with One Group Pre-test and Post-test design. Data collection was carried out through tests with research subjects, namely six teachers from two elementary schools in Sumedang Regency. The results of this study indicate an increase in teachers' understanding of the learning characteristics of students with special needs with a percentage of 59.61%. So it can be concluded that learning videos are effective in increasing teachers' understanding of students with special needs. The recommendation is that teachers can use interactive learning videos to help fulfill the learning needs of students with special needs in elementary schools.